Analisis Implementasi Pelaksanaan Program Ringkas, Rapi, Resik, Rawat, Rajin (5R) di PT X Proyek pada Proyek X - Armanda Febriadana Dilaksa; Ida Umarul Mufidah; Octovianus Bin Rojak (STIKes Ibnu Sina Ajibarang, 2025)
Based on data from the Employment Social Security Agency, the number of work accidents in Indonesia reached 234,270 cases, of which around 31.9% occurred in the construction sector which is known to have high risks. PT X as a contractor company also recorded several accident reports (Accident Report) from December 2023 to June 2024, including cases of being stabbed with sharp objects, near misses, and placement of items that do not meet standards. This shows the importance of implementing housekeeping procedures as regulated in the Minister of Manpower Regulation No. 5 of 2018 concerning Environmental Occupational Safety and Health, specifically Article 5 paragraph 3. This study aims to examine the factors that most influence the implementation of the Ringkas, Rapi, Resik, Rawat, Rajin (5R) program on Project X at PT X. Using a qualitative method through a case study approach, data was collected through interviews, observations, and documentation. The results of the study showed that the Concise aspect obtained a score of 85% (Satisfactory), Neat 75% (Satisfactory), Clean 90% (Very Satisfactory), Maintain 83% (Satisfactory), and Diligent only 64% (Needs Improvement). The average implementation of the 5R program in the company reached 79.4%, categorized as good, although the Diligent aspect remains a major weakness. This condition emphasizes that the company needs to strengthen supervision in the field and increase employee awareness to consistently implement the 5R principles. Efforts that can be made include holding regular training on 5R, increasing periodic monitoring, and providing educational media such as posters or information boards that are easy for workers to understand. With this strategy, it is hoped that the implementation of the 5R program can be more optimal, employee awareness will increase, and the risk of workplace accidents can be minimized to create a safer, more orderly, and more productive work environment.